The exploration of aza-quinolines as hematopoietic prostaglandin D synthase (H-PGDS) inhibitors with low brain exposure. Issue 23 (1st December 2020) - Cadilla, Rodolfo; Deaton, David N.; Do, Young; Elkins, Patricia A.; Ennulat, Daniela; Guss, Jeffrey H.; Holt, Jason; Jeune, Michael R.; King, Andrew G.; Klapwijk, Jan C.; Kramer, H. Fritz; Kramer, Nicholas J.; et al.
Graphical abstract: Abstract: GlaxoSmithKline and Astex Pharmaceuticals recently disclosed the discovery of the potent H-PGDS inhibitor GSK2894631A 1a (IC50  = 9.9 nM) as part of a fragment-based drug discovery collaboration with Astex Pharmaceuticals. This molecule exhibited good murine pharmacokinetics, allowing it to be utilized to explore H-PGDS pharmacology in vivo . Yet, with prolonged dosing at higher concentrations, 1a induced CNS toxicity. Looking to attenuate brain penetration in this series, aza-quinolines, were prepared with the intent of increasing polar surface area. Nitrogen substitutions at the 6- and 8-positions of the quinoline were discovered to be tolerated by the enzyme. Subsequent structure activity studies in these aza-quinoline scaffolds led to the identification of 1, 8-naphthyridine 1y (IC50  = 9.4 nM) as a potent peripherally restricted H-PGDS inhibitor. Compound 1y is efficacious in four in vivo inflammatory models and exhibits no CNS toxicity.